Muscle metabolism, temperature, and function during prolonged, intermittent, high-intensity running in air temperatures of 33 ° and 17 °C - Morris, J. G.; Nevill, M. E.; Boobis, L. H.; Macdonald, I. A.; Williams, C. (International Journal of Sports Medicine, 2005)
Nine unacclimatized university sportsmen performed a prolonged, intermittent, high-intensity shuttle running test in hot (HT) (33 °C, dry bulb temperature, ~ 28 %, relative humidity) and moderate (MT) (17 °C, 63 %) environmental conditions. Subjects performed 60 m of walking, a 15-m sprint, 60 m of cruising (~ 85 % V·O2max), and 60 m of jogging (~ 45 %V·O2max) for 14.8 ± 0.1 min followed by a 3-min rest, repeated until volitional exhaustion. The hot trial was performed first followed, 14 days later, by the moderate trial. During exercise subjects drank water ad libitum. Subjects ran almost twice as far in the moderate as in the hot trial (HT 11216 ± 1411, MT 21644 ± 1629, m, p < 0.01), and the decline in average 15-m sprint performance was greater in the heat (HT, 0.17 ± 0.05, MT, 0.09 ± 0.03, s, p < 0.05). Average heart rates, blood lactate and glucose, and plasma adrenaline and noradrenaline concentrations were greater in the HT (main effect trial, p < 0.01), as were serum cortisol concentration (main effect trial p < 0.05, n = 5) and muscle temperature (HT exhaustion vs. same time point in MT, 40.2 ± 0.3 vs. 39.3 ± 0.2, °C, p < 0.01). Peak torque during knee flexion and extension was not different pre-and post-exercise in the HT. Muscle glycogen utilization tended to be greater in the heat (HT 193.2 ± 19.5, MT 143.8 ± 23.9, mmol · kg dry wt-1, p = 0.055, n = 8). In 7 out of the 8 subjects the increase in utilization was between 19 and just over 200 % greater in the HT. Glycogen remaining in the muscle at exhaustion was greater in the hot than moderate trial (HT 207.4 ± 34.3, MT 126.5 ± 46.8, mmol · kg dry wt-1, p < 0.01, n = 8). Rectal temperature (Trec) was higher in the HT at exhaustion than at the same point in time in the moderate trial (HT, 39.60 ± 0.15 vs. MT 38.75 ± 0.10, °C, interaction trial-time, p < 0.01). There was a very strong negative relationship between rate of rise in Trec and distance completed in the HT (HT r = - 0.90, p < 0.01, MT r = - 0.76, p < 0.05). Thus, the earlier onset of exhaustion during prolonged intermittent shuttle running in the heat is associated with hyperthermia. However, while muscle glycogen utilization may be elevated by heat stress, low whole muscle glycogen concentrations would not seem to be the cause of this earlier exhaustion.